Aggregatibacter actinomycetemcomitansas indicator for aggressive periodontitis by two analysing strategies - Beate Schacher (Blackwell Synergy, 2007)
Objective: To compare the subgingival microbiota of aggressive and chronic periodontitis (ChP) using single-site and pooled plaque samples. Methods: In 60 patients with aggressive or ChP, subgingival plaque was sampled from the four deepest pockets using two sterile paper points simultaneously. One paper point from each pocket was put in a separate transport vial, the second was pooled with the three other paper points of a respective patient. The content of each vial was analysed for Aggregatibacter actinomycetemcomitans, Tannerella forsythensis, Porphyromonas gingivalis, and Treponema denticola. Results: Pooled plaque samples detected higher numbers for all tested pathogens than single-site samples. Detection frequencies were similar for both strategies. Using single-site samples, A. actinomycetemcomitans detection rate was statistically significantly a higher in aggressive than in ChP (p50.01). A. actinomycetemcomitans was found in higher numbers, the other pathogens in lower numbers in aggressive than in ChP. Neither presence nor absence of one of the tested bacteria had sufficient positive or negative predictive value for aggressive periodontitis. Conclusion: A. actinomycetemcomitans was detected in higher numbers and frequency in aggressive than in ChP. Its detection may confirm the clinical diagnosis and influence therapy. As a diagnostic test, its sensitivity and predictive value was low.